Review of: George Steinmetz, The Colonial Origins of Modern Social Thought: French Sociology and the Overseas Empire (Princeton NJ: Princeton University Press, 2023). - Flemmen, Magne P. (Serendipities. Journal for the Sociology and History of the Social Sciences, 2024)
-